2021
DOI: 10.1016/j.ebiom.2021.103557
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the gut mycobiome in patients with MS

Abstract: Background The mycobiome is the fungal component of the gut microbiome and is implicated in several autoimmune diseases. However, its role in MS has not been studied. Methods In this case-control observational study, we performed ITS sequencing and characterised the gut mycobiome in people with MS (pwMS) and healthy controls at baseline and after six months. Findings The mycobiome had significantly higher alpha diversity and inter-subject var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
(64 reference statements)
0
36
1
Order By: Relevance
“…Previous mycobiome studies frequently reported that Saccharomyces was one of the most prevalent fungi in the human gut ( 18 , 37 , 39 , 43 , 44 ). Our present study also demonstrated that it was one of most abundant fungi in the participants’ gut, especially in the CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mycobiome studies frequently reported that Saccharomyces was one of the most prevalent fungi in the human gut ( 18 , 37 , 39 , 43 , 44 ). Our present study also demonstrated that it was one of most abundant fungi in the participants’ gut, especially in the CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In pwMS, specific bacterial taxa related to proinflammatory responses are favored ( 12 ) while short-chain fatty acid (SCFAs)-producing bacteria are reduced ( 11 ). Interestingly, researchers are also starting to link MS to a fungal etiology, having revealed the presence of mycotoxins, IL-17, chitotriosidase, and antibodies against fungi ( 13 , 14 ) in persons with MS (pwMS). Indirectly, alterations of intestinal permeability (IP) have also been detected in relapsing-remitting MS (RR-MS) patients ( 15 ), with zonulin being recognized as a peripheral marker of IP and blood–brain barrier (BBB) in MS ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the gut bacterial microbiota structure have been well studied in metabolic diseases such as gestational diabetes mellitus (GDM) ( Wu et al, 2021 ), type 2 diabetes ( Bielka et al, 2022 ) and obesity ( Turnbaugh et al, 2009 ), and an increasing number of reports suggest that gut commensal fungi, as an important component of the intestinal microbiome, also influence host metabolic homeostasis ( Shah et al, 2021 ; Zhang et al, 2021 ). Recent studies indicate that commensal fungi have the potential to influence host metabolism directly.…”
Section: Introductionmentioning
confidence: 99%